The mean value of the maximum ACC for each number of added edges k for 10 runs acquired by MOEA/D-SW, MA-SW, GA-SW, GR-SW, NW model, and NSGA-II. - Ruochen Zhang (3434996) (2024)
(a) and (b) are the results on the regular and the random networks, respectively.